2021
DOI: 10.46939/j.sci.arts-21.2-a15
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Wave Solutions of Some Conformable Time-Fractional Coupled Systems via an Analytic Approach

Abstract: The main purpose of this research is to inquire the new solitary wave solution of the coupled time-fractional models to validate the influence and proficiency of the planned variational iteration method (VIM) using conformable derivative definition. Applications to four demanding nonlinear problems like Hirota-Satsuma coupled KdV equations, modified Boussinesq (MB) equation, approximate long wave (ALW) equation and Drinfeld-Sokolov-Wilson (DSW) equation demonstrate the efficiency and the robustness of the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Consider the solution in fractional Taylor series (10) The recurrence relation for non-linear source term is (11) where represents Adomian polynomial defined by (6) Thus, the required solution is obtained by (12)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consider the solution in fractional Taylor series (10) The recurrence relation for non-linear source term is (11) where represents Adomian polynomial defined by (6) Thus, the required solution is obtained by (12)…”
Section: Methodsmentioning
confidence: 99%
“…Linear and non-linear FODEs have been solved using different methods in this regard. In [9], for example, has a discussion of the modified Bernoulli sub-equation and non-linear time fractional Burgers equations. In [10,11] was carried out a computational simulation of space fractional diffusion equations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various effort follows in [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] to learn the profound subjective alteration during really nonlinear marvel brought about by the simply nonlinear dispersive model. Rosenau and Hyman [2]…”
Section: Introductionmentioning
confidence: 99%
“…In any case, Kivshar [9] anticipated the presence of split compaction, someplace he demonstrated that fracture with conservative help may exist in a cross-section of an equal particle using an incompatible coupling. Kivshar [9] examined the following models:…”
Section: Introductionmentioning
confidence: 99%